素養導向國教新課綱的師資培育：國立臺灣大學「探究式─素養導向的師資培育」理想芻議 Teacher Preparation in Response to Competence-Based Curriculum Reform for K-12 Education: National Taiwan University's Proposal of Inquiry-Based and Competence-Based Teacher Education - 符碧真 Bih-Jen Fwu (National Taiwan Normal University, 2018)
新課綱強調核心素養，是史上最大規模的課程改革，自108 學年度起上路。為培育新課綱所需的師資，2017年公布的《師資培育法》規定教育部要訂定「教師專業素養指引」及「師資職前教育課程基準」。師資培育機構須根據這些規定，自行規劃課程，並自108 學年度起實施，這對師資培育機構是很大的挑戰。本研究探討兩個問題：一、新課綱強調「核心素養」，新《師資培育法》強調教師「專業素養」，一時之間素養成為「顯學」，究竟何謂「素養」？ 有無同時適用於中、小學教育及教師專業的素養定義？素養為何如此重要？二、師資培育機構該如何規劃職前教育課程，以培育新課綱所需的師資？本研究指出素養包括「功能性素養」及橫跨各學科的「共通性能力」，藉由知識與真實情境的連結，可培養素養，並減少學生「學這要幹嘛」及「學這有何用」的疑問，以提升學習動機。此外，本研究根據學理，提出國立臺灣大學「探究式─素養導向的師資培育」理想芻議，希望拋磚引玉，引發學界對話，為108 學年度新課綱及新師資培育課程同步實施做好準備。 A large-scale curriculum reform for K-12 education that emphasizes the cultivation of core competencies will be launched in 2019. To prepare future teachers for this reform, teacher education institutions (TEIs) are required to restructure their curriculum by 2019 in accordance with the "core competencies for teachers" and "standards for pre-service teacher education" specified by the new Teacher Education Act. "Core competencies" has become a jargon commonly used in discussions of K-12 and teacher education; however, its definition remains unclear. This paper investigated (1) whether a common definition of core competencies exists for both K-12 education and teacher education, and why core competencies have reached their current level of prominence; and (2) how TEIs have restructured their new curriculum to meet K-12 educational requirements. The results revealed that core competencies are defined as functional literacy and transversal competence, linking academic knowledge to real-life experience. Moreover, National Taiwan University proposed a restructuring of the teacher education curriculum based on theoretical reasoning of teacher education. It is believed that clarifying the definition of core competencies and the proposed plan may provoke discussions among educators in TEIs regarding implementing a curriculum reform in 2019 for both K-12 education and teacher education.